The Ultimate MacAddict Holiday Gadgets Guide. - Lu, Cathy (Macaddict : a better machine, a better magazine.)
We dug up the absolute coolest gifts (both Mac and PC) for the music lover, videographer, road warrior, and Mac addict in your life. They're so cool, you'll want to keep them for yourself.